PERANAN KELOMPOK SEL TERHADAP PERTUMBUHAN GEREJA HOME COMMUNITY CHURCH (HCC) DI JEMAAT PALU - Nustince Maki; Purnama Pasande; Oskar Sopang; Niel Parinsi (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2021)
The church wants the congregation's spirituality to experience growth. The number of membership is decreasing. At Home Community Church (HCC) Palu, a small group performs the process of renewal, leading to the likeness of Christ and training men to become fishers of men. Through small groups (Komsel), it is hoped that the congregation's growth will increasingly have a positive effect on the communion and church growth. The respondents were 144 Komsel members from a total population of 212 members. The method used in this study is a quantitative method with a Likert scale questionnaire as a research instrument. In this study, the role of Komsel significantly affects the number of HCC church congregations and provides benefits in service, evangelizing, teaching, and communion programs.